2006
DOI: 10.1002/masy.200651107
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of The Rheological Properties of Bimodal Emulsions

Abstract: The model of Ouchiyama and Tanaka [1][2][3] was successfully adapted to calculate the maximum packing fraction (f m ) of polymer latexes with varying bimodal particle size distributions based upon rheological measurements performed on its constituent parts. The values of f m calculated from the model can be used to predict the rheological properties of the latices. The model was experimentally validated and used for the prediction the viscosity of studied bimodal latices of known concentration using the master… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…[], Barnes [], Pishvaei et al . [], and Qi and Tanner []. Most of these studies have analyzed (a) bimodal suspensions in which the main solid phase is represented by spheres of a coarse size and (b) the effect of particle size ratio on the viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…[], Barnes [], Pishvaei et al . [], and Qi and Tanner []. Most of these studies have analyzed (a) bimodal suspensions in which the main solid phase is represented by spheres of a coarse size and (b) the effect of particle size ratio on the viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…(16) should not be mistaken for a rigorous model, the expression quantifies an important observation in electrostatically stabilized systems: for constant surface coverage conditions, large particles can be packed closer together than smaller particles. Experimentally it has been observed that for a constant volume fraction of polymer, latexes comprised of small particles will be more viscous than latexes comprised of large particles [32]. However, Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The packing model developed by Pishvaei et al [32] has been extended to provide a means of estimating the rheological parameters of broader, more realistic PSDs. The utility of the framework is demonstrated by using the zone-byzone PSD information to explain some of the trends seen in the time-evolution of the volume-averaged PSDs and the PSD of the final product.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations